Perception and Attitudes Toward PPE-Related Waste Disposal Amid COVID-19 in Bangladesh: An Exploratory Study - Islam, S. M. Didar-Ul; Safiq, Mariam Binte; Bodrud-Doza, Md.; Mamun, Mohammed A. (Frontiers in Public Health, 2020)
Personal protective equipment (PPE) are essential items to protect from the exposure of infectious pathogens or contaminants, which are frequently used at health care settings and public spheres since the COVID-19 outbreak. There is no prior study investigating public perception and attitudes towards PPE related waste disposal in Bangladesh. Hence, an online survey was carried out among 1,303 Bangladeshi adult residents to explore the issue. Results stated that face mask and hand gloves were widely used PPE, where around 45.50% mask and 31.60% hand gloves were disposable. Approximately 94.50% of the participants precepted to use at least one type of PPE while going outside. Only 18.65% of the respondents precepted to burn the PPE related waste, while most of them reported other less protective disposal measures. Females, urban residents and participants with higher education were found having better perception and attitudes towards PPE related waste disposal. As being the first exploratory study in the country, the present findings are anticipated to be helpful in policy levels in respect to arranging awareness programs.